Effect of 30 days of ketogenic Mediterranean diet with phytoextracts on athletes' gut microbiome composition - Mancin, Laura; Amatori, Stefano; Caprio, Massimiliano; Sattin, Eleonora; Bertoldi, Loris; Cenci, Lorenzo; Sisti, Davide; Bianco, Antonino; Paoli, Antonio (Frontiers in Nutrition, 2022)
Recent research suggest that gut microbiome play a fundamental role in athlete’s health and performance. Interestingly, nutrition can affect athletic performance by influencing the gut microbiome composition. Among different dietary patterns, ketogenic diet represents an efficient nutritional approach to get adequate body composition in athletes, however, some concerns have been raised about its potential detrimental effect on gut microbiome. To the best of our knowledge, only one study investigated the effect of ketogenic diet on the gut microbiome in athletes (elite race walkers), whilst no studies are available in a model of mixed endurance/power sport such as soccer. This study aimed to investigate the influence of a ketogenic Mediterranean diet with phytoextracts (KEMEPHY) diet on gut microbiome composition in a cohort of semi-professional soccer players. Methods: 16 male soccer players were randomly assigned to KEMEPHY diet (KDP n=8) or western diet (WD n=8). Body composition, performance measurements and gut microbiome composition were measured before and after thirty days of intervention by 16S rRNA amplicon sequencing. Alpha-diversity measures and PERMANOVA was used to investigate pre-post differences in the relative abundance and Spearman’s correlations to investigate associations between microbial composition and macronutrient intake. Linear discriminant analysis was performed on the post-intervention data. Results: No differences were found between pre and post- dietary intervention for microbial community diversity. Post-hoc paired Wilcoxon test showed a significant time×group effect for Actinobacteriota (p=0.021, ES=0.578), which increased in the WD group and decreased in the KEMEPHY group. At genus level, Bifidobacterium, Butyricicoccus and Acidaminococcus genera were more abundant in the WD group, while Clostridia UCG-014, Butyricimonas, Odoribacterter and Ruminococcus genera were more abundant in the KEMEPHY group. Our results demonstrate that thirty days of KEMEPHY intervention, in contrast with previous research, do not modify the overall composition of gut microbiome in a cohort of athletes. KEMEPHY diet may represent a safety tool for maintaining and/or regulating the composition of gut microbiome in athletes. Due to the fact that not all ketogenic diets are equal, we hypothesized that each version of ketogenic diet, with different kind of nutrients or macronutrients partitioning, may differently affect the human gut microbiome.